Journal-Conference Interaction and the Competitive Exclusion Principle - Grudin, Jonathan (ACM Interactions, 2013)
Each biological species occupies a unique ecological niche—usually. Occasionally one species invades another’s niche, arriving as a stowaway on a boat, in a tourist’s luggage, floating on a log, or crawling across a newly formed land bridge. What happens when two species occupy the same niche? Biologists agree: One is soon gone.